The plasminogen protein is associated with high myopia as revealed by the iTRAQ-based proteomic analysis of the aqueous humor - Kai Wen (Nature Portfolio, 2021)
Abstract To explore the pathogenesis of high myopia (HM) using quantitative proteomics. The aqueous humor of patients with simple nuclear cataract and nuclear cataract complicated with HM (hereinafter referred to as “C” and “HM” groups, respectively) were collected. The isobaric tags for relative and absolute quantitation (iTRAQ)-based liquid chromatography–tandem mass spectrometry (LC–MS/MS) proteomics approach was employed to explore differentially expressed proteins (DEPs). Bioinformatics was used to interpret the proteomic results. Furthermore, the plasminogen (PLG) protein was confirmed by enzyme-linked immunosorbent assay (ELISA) as the candidate biomarker for HM through a receiver operating characteristic curve analysis. The study showed 32 upregulated and 26 downregulated proteins. The gene ontology analysis demonstrated that 58 DEPs corresponded to 325 biological processes, 33 cell components, and 45 molecular functional annotations. The Kyoto Encyclopedia of Genes and Genomes analysis showed that the upregulated DEPs were highly enriched in the coagulation and complement cascades, consistent with the gene set enrichment analysis. Our data suggested that some DEPs might be hallmarks of the development of HM. ELISA confirmed that the PLG expression levels were significantly upregulated in HM. This was a new study investigating alterations in protein levels and affected pathways in HM using iTRAQ-based quantitative proteomics. Our study provided a comprehensive dataset on overall protein changes and shed light on its potential molecular mechanism in human HM.